Proposta para implantação da manutenção enxuta - Munaro, André Felipe (2018)
The industrial maintenance department has a responsibility for the proper preservation of the assets and its management has become a prominent issue in the competitive global market. The great expansion of lean manufacturing concepts shows the possibility of gains in the most diverse areas, including the industrial maintenance department. This work proposed a roadmap for the development and implementation of lean maintenance in companies through a framework based on literature. Other frameworks, flowcharts and work-related scripts were taken into account, as well as the inclusion of the premises of the process approach and observations collected in a pilot evaluation with specialists from a metal mechanic company, with which particularities were demonstrated to be considered and your interests in the application. Then, the adjusted script was proposed to verify specialists from 6 companies, and semi-structured interviews were used. The qualitative analysis of the data obtained results from six companies of diverse branches that should be considered in the implantations, showing difficulties such as lack of identification of equipment, preventive maintenance, absence of culture of waste study, training, 5S and TPM, widely discussed in the literature, showing the particularities associated with this specific area, as well as the potential of implementation of the philosophy and its difficulties.